Optimization of air traffic service route networks with intersection angle constraints - N. N. Hoang Quan; V. N. Nechaev; R. A. Subbotin (Научный вестник МГТУ ГА, 2025)
On a daily basis, thousands of aircraft move through the airspace, with their management entrusted to specialized teams of specialists from Air Navigation Service Providers (ANSPs). To ensure effective and efficient air traffic management (ATM), ANSPs continually develop innovative methods to modernize and automate the processes involved in ATM. One of the key areas of focus in this effort is the optimization of air traffic service route networks, which contributes to increasing airspace capacity, reducing congestion, and enhancing the efficiency of air traffic services. This paper proposes a model for ATS route network optimization using the A-star algorithm to minimize route distances. The study analyzes three key scenarios, considering the presence and absence of angle constraints at route intersection points. Optimizing the ATS route network provides substantial benefits in enhancing the quality of ATM services and reducing operational costs for airlines. The model has been successfully implemented within the Ho Chi Minh Area Control Center (ACC HCM) airspace. The results of the model's application demonstrate its high efficiency and practical value, particularly in airspaces with high traffic density.